Endovascular Stroke Therapy - Caganap, Scott D.; Smith, Wade S. (Seminars in Thrombosis and Hemostasis, 2017)
Acute ischemic stroke therapy has rapidly evolved over the past two decades. Recently, a paradigm shift has occurred in the treatment of acute ischemic stroke due to large vessel occlusion with the publication of several randomized trials proving that mechanical thrombectomy with stent retriever devices improves clinical outcome in comparison to intravenous thrombolysis. Furthermore, pooled data from the clinical trials suggest that mechanical thrombectomy can improve outcome in a broad range of patients, and that the sooner the intervention can be performed, the greater the benefit. Delays in endovascular stroke therapy can occur during multiple time points during a patient's encounter, and these time delays are associated with worse outcomes. This association emphasizes the importance of enhancing speed-of-care processes in patients undergoing endovascular reperfusion. Efforts to reduce time delays in endovascular stroke treatment can be achieved by reflecting on the health care initiatives that took place for the treatment of acute myocardial infarction almost 20 years ago. The ideal system of care to reduce delays in endovascular stroke therapy will likely include rapid transport of all eligible patients directly to the angiography suite to bypass the inefficiencies of workflow during the early inhospital setting. These strategies will undoubtedly take time to implement, as they require further research, infrastructure funding, and policy changes at local, regional, and national levels.
Keywords: endovascular therapy; acute ischemic stroke; mechanical thrombectomy/embolectomy; stent retriever